(untitled) - Maya Bessarav (Hà Nội, 1978)
Soviet physicist. Did fundamental theoretical work in low-temperature physics, predicting properties for a rare helium isotope that scientist are still trying to verify; awarded Nobel Prize in physics, 1962
Keywords: physicians - biography